A comparative Life Cycle Assessment of external wall-compositions for cleaner construction solutions in buildings. (15th June 2016) - Ingrao, Carlo; Scrucca, Flavio; Tricase, Caterina; Asdrubali, Francesco
Abstract: Application of Life Cycle Assessment (LCA) in buildings is usually performed at the envelope scale, mainly for comparison of several sample-solutions, and provides in-depth analyses of the related energy and environmental performances. In this way, it is possible to identify those solutions that perform best in energy and environmental terms, and that so are suitable for construction of sustainable buildings. In this context, the study was aimed at carrying out energy and environmental assessments to compare four external-wall samples characterised by different rates of sophistication in terms of assembly technologies and component materials. The samples considered were properly designed for development of the subsequent energy-environmental analysis. In particular, two "standard" wall compositions and two ventilated façades were considered, using rock-wool and recycled Polyethylene Terephthalate (R-PET) as insulating materials. The study documented that, as regards both energy and environmental impacts, ventilated façades perform quite well compared to the "standard" wall compositions, especially when equipped with R-PET. It also confirmed that both solutions easy to be disassembled and recycled materials are key design choices for environmental sustainable and low energy demanding buildings along their whole life cycles. Finally, the authors believe that the study provides helpful insights on the environmental sustainability of eco-friendly materials and technologies, and can contribute to less time and resources consuming LCAs at the building scale. Highlights: Four wall compositions, including two ventilated façades (VFs), were designed. Usage of panels made of recycled Polyethylene Terephthalate (R-PET) was tested. Energy and environmental evaluations were performed by Life Cycle Assessment (LCA). R-PET usage enabled higher energy and environmental performance in VFs. The study showed the importance of LCA as a support tool to building design.